Au‐Decorated Cracked Carbon Tube Arrays as Binder‐Free Catalytic Cathode Enabling Guided Li2O2 Inner Growth for High‐Performance Li‐O2 Batteries. (16th September 2016) - Tu, Fangfang; Hu, Junping; Xie, Jian; Cao, Gaoshao; Zhang, Shichao; Yang, Shengyuan A.; Zhao, Xinbing; Yang, Hui Ying
Abstract : Owing to their extremely high energy density, Li‐O2 batteries have attained increasing attention in recent studies. However, deposition of the discharge product, insulating Li2 O2, is known to seriously limit the electrochemical performance of Li‐O2 batteries. While extensive studies have focused on relieving electrode deactivation by controlling Li2 O2 growth, no permanent or effective mechanism is delivered. Here, a unique design comprising a catalytic cathode constructed by cracked carbon submicron tube (CST) arrays decorated with Au nanoparticles on inner walls is proposed. The introduction of Au nanoparticles not only improves electrode conductivity but also provides catalytic sites, guiding conformal growth of thin‐layered Li2 O2 inside the cracked CST. Density functional theory calculations support that Au decoration on CST favors the conformal growth of Li2 O2 on inner tubular walls. This growth behavior of Li2 O2 renders easy decomposition of Li2 O2, prevents carbon tube electrode from full, rapid deactivation, and preserves the free space for reactants transport. Li‐O2 cells with Au@CST exhibit good rate capability (1208 mAh g –1 at a high current density of 1000 mA g –1 ) and long cycle life (112 cycles at a current density of 400 mA g –1 with a limited capacity of 500 mAh g –1 ). Abstract : Ni‐supported carbon submicron tube arrays with Au decorated on the inner walls (Au@CST) catalyze conformal growth of thin‐layered Li2 O2 on the inner walls, leading to a high capacity and long cycle life of Li‐O2 cells. The Li‐O2 cell with an Au@CST array cathode maintains a stable cycling of 112 times under 400 mA g –1 at 500 mAh g –1 .